Hybrid administrative traditions in Macao SAR: Between Napoleonic and Chinese administrative traditions - Faria, J. C. C.; Santiago, A. R. (JANUS.NET, e-journal of International Relations, 2026)
Macao is a Special Administrative Region of the People's Republic of China, governed by the principle of ‘One Country, Two Systems’. With a Portuguese historical legacy lasting more than 400 years, which continued until December 1999, we consider that the Region has a very particular model of public administration and is undergoing a gradual process of administrative reform, which is the subject of this article. Its public administration is not limited to a linear continuation of the Portuguese period, nor is it a simple transposition of the administrative model of the People's Republic of China; rather, it is a hybrid configuration, in which the Napoleonic legacy (of Portuguese origin) provides a resilient legal-administrative support, recontextualized by a post-1999 political-administrative logic associated with the Chinese administrative tradition (of Confucian origin). The results point to a configuration in which the legal and administrative support remains predominantly Napoleonic (legalism, uniformity, legal and administrative control mechanisms), while the political logic shows Confucian traits (centrality of the executive, vertical accountability and primacy of stability). We conclude that Macao exhibits a relatively stable hybrid model, resulting from the coexistence and recombination of distinct (but also similar) administrative traditions, with incremental adaptations that preserve the inherited legalistic basis and simultaneously reinforce political coordination mechanisms typical of the Chinese context.